Baba Rafi's Supply Chain Method to Maintain Good Product: A Case Study - Albertus Gondokusumo; Christofer Alimwijono; Liem Gai Sin (AIBPM Publisher, 2018)
This paper analyzes the supply chain system inside Baba Rafi's logistics. The purpose of the paper is to create an example of franchises supply chain management framework which is useable to the same type of industry. The research is a qualitative descriptive. Our methods to gain qualitative data are from interviews and questionnaire from Baba Rafi’s Outlets on the city of Malang, Indonesia. Another secondary data are gained from journals, reports, and also articles.The outcome of the research is to analyse the aspectsthat affect the supply chain management of Baba Rafi’s. Keywords – franchise, logistics, supply chain, method, good product.